2018
DOI: 10.1136/vr.104535
|View full text |Cite
|
Sign up to set email alerts
|

Zoonotic bacteria and parasites found in raw meat‐based diets for cats and dogs

Abstract: Feeding raw meat-based diets (RMBDs) to companion animals has become increasingly popular. Since these diets may be contaminated with bacteria and parasites, they may pose a risk to both animal and human health. The purpose of this study was to test for the presence of zoonotic bacterial and parasitic pathogens in Dutch commercial RMBDs. We analysed 35 commercial frozen RMBDs from eight different brands. serotype O157:H7 was isolated from eight products (23 per cent) and extended-spectrum beta-lactamases-produ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

6
137
5
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 146 publications
(150 citation statements)
references
References 41 publications
(82 reference statements)
6
137
5
2
Order By: Relevance
“…As the study by van Bree and others shows, 14 RMBDs pose a hazard to public health as well as to animals. The study should be a stimulus for further epidemiological studies to produce additional evidence on the safety and risks related to RMBDs in European countries and beyond.…”
mentioning
confidence: 97%
See 3 more Smart Citations
“…As the study by van Bree and others shows, 14 RMBDs pose a hazard to public health as well as to animals. The study should be a stimulus for further epidemiological studies to produce additional evidence on the safety and risks related to RMBDs in European countries and beyond.…”
mentioning
confidence: 97%
“…As dogs and cats infected with pathogenic bacteria may shed these pathogens via faeces, there is a risk of zoonotic transmission to people 17,18 . Van Bree and others 14 thus showed that the feeding of RMBDs poses a serious risk to animal and public health due to its microbial load.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…The van Bree paper 1 that Davies refers to does not perform a risk analysis; therefore, it does not, as he suggests, raise public awareness about the potential risks of raw food feeding. It will stoke fears counter to the experience of hundreds of vets and millions of dog owners around the world who are successfully and responsibly feeding/being fed raw food.…”
mentioning
confidence: 99%